THE ENHANCEMENT OF FEATURED SPORTSPROCEDURES AND EVALUATIONQUALITY IN LANDAK REGENCY - Maharani Fatima Gandasari (Universitas Negeri Medan, 2017)
Abstract This study aims to determine the sport coaching whichbecomes priorityas featured sports and to disclose any matters related to the improvement of procedures and evaluation of featured sportsin Landak Regency. This research was sportsaction research. The population in this study was the athletes in the featured sport in Landak Regency. The subjects included two sports that became first and second featured sports in Landak Regency. The data was collected through interviews and observation. The results show that the prioritized order of the featured sports inLandak Regency is as follow 1) Athletic, 2) Karate, 3) Boxing and 4) Judo. Although the enhancement of the featured sport in the regency has currently been prioritized, the recruitment of athletes in Athletics and Karate has not fully started at early age. Therefore, sport coaching has not been conducted optimally by the respective local government. Based on the study, the constraints for the coaching program include inadequate sport infrastructures and limited transportation, especially for athletes who come remote villages. Therefore, they do not get opportunity to join the selection and sport events in Landak Regency. The process of coaching has been carried out by monitoring the development of athletes through physical and performance testsof each athlete. However, the tests have not been done systematically and periodically. From the description above, the study concludes that it is necessary to improve the quality of procedure and evaluation of athletes in the featured sports through the process of sports coaching in landak Regency. Keywords: Featured Sports, Coaching, Landak Regency.